2006
DOI: 10.1593/neo.06559
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of ZO-1 and ZO-2 in Sertoli Cells and Loss of Blood-Testis Barrier Integrity in Testicular Carcinoma In Situ

Abstract: Carcinoma in situ (CIS) is the noninvasive precursor of most human testicular germ cell tumors. In normal seminiferous epithelium, specialized tight junctions between Sertoli cells constitute the major component of the blood-testis barrier. Sertoli cells associated with CIS exhibit impaired maturation status, but their functional significance remains unknown. The aim was to determine whether the blood-testis barrier is morphologically and/or functionally altered. We investigated the expression and distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…Other techniques have been employed for this, such as IHC to locate proteins in particular cell types (27,28). More recent studies have applied proteomic techniques to the human testis that have indicated differences in proteins present in the testes of normozoospermic men and those with nonobstructive azoospermia (12), increases in apoptotic pathways when spermatogenesis is halted by hormonal contraception (14) and the large heterogeneity of proteins in fertile men (13).…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques have been employed for this, such as IHC to locate proteins in particular cell types (27,28). More recent studies have applied proteomic techniques to the human testis that have indicated differences in proteins present in the testes of normozoospermic men and those with nonobstructive azoospermia (12), increases in apoptotic pathways when spermatogenesis is halted by hormonal contraception (14) and the large heterogeneity of proteins in fertile men (13).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in mammals like in Drosophila, spermatogenesis depends on interactions between supportive Sertoli cells and germ cells [42]. Moreover, inactivation of the Dlgh-1 gene in mice produces various abnormalities in their renal and urogenital organs with hypoplasia of kidneys and ureters, and absence of vagina and seminal vesicle [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…ZO-2 shuttles from the cell periphery to the nucleus (Islas et al 2002;Traweger et al 2003;Kausalya et al 2004), interacts with the nuclear ribonucleoprotein scaffold attachment factor-B (SAF-B) (Traweger et al 2003) and several transcription factors (Betanzos et al 2004;Huerta et al 2007). ZO-2 inhibits cell proliferation by affecting transcription, translation, and degradation of cyclin D1 (Huerta et al 2007;Tapia et al 2009), coincident with observations that its expression is reduced in certain tumors (Chlenski et al 2000;Fink et al 2006;Paschoud et al 2007). ZO-2 binds and inactivates oncogenic viral proteins Lee et al 2000;Glaunsinger et al 2001), and its degradation is induced by HIV type 1 gp120 (Nakamuta et al 2008).…”
Section: Zo-2 In Cell Proliferation and Gene Expressionmentioning
confidence: 91%